Adjuvant Chemotherapy Benefit in Elderly Stage II/III Colon Cancer Patients - Chen, Xin; Tu, Junhao; Xu, Xiaolan; Gu, Wen; Qin, Lei; Qian, Haixin; Jia, Zhenyu; Ma, Chuntao; Xu, Yinkai (Frontiers in Oncology, 2022)
Background Studies providing more evidence to guide adjuvant chemotherapy decisions in elderly colon cancer patients are expected. Methods We obtained data from the Surveillance, Epidemiology and End Results (SEER) database between 2004 and 2012. Kaplan-Meier survival curves were constructed to calculate the cancer-specific survival (CSS) rate, and comparisons of survival difference between different subgroups were performed using the log-rank test. Multivariate Cox proportional hazards regression models were carried out to estimate hazard ratio (HR) and 95% confidence intervals (CIs) of different clinicopathological characteristics. Results In stage II colon cancer patients aged 70 years or older, the Kaplan-Meier survival analysis showed that the 5-year CSS rates of no chemotherapy and chemotherapy groups were 82.0% and 72.4%, respectively (P < 0.001). In stage III colon cancer patients aged 70 years or older, the Kaplan-Meier survival analysis showed that the 5-year CSS rates of no chemotherapy and chemotherapy groups were 50.7% and 61.3%, respectively (P < 0.001). Patients with chemotherapy receipt were independently associated with a 35.8% lower cancer-specific mortality rate (HR = 0.642, 95% CI: 0.620-0.665, P < 0.001) compared with those who did not receive chemotherapy. Conclusions Adjuvant chemotherapy should be considered during the treatment of stage III colon cancer patients aged 70 years or older, but the chemotherapy benefit in elderly stage II colon cancer is suboptimal.